2011
DOI: 10.5897/ajmr11.806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different concentrations of bacterial suspensions on biocontrol efficacy and storage stability of Bacillus cereus AR156, Pantoea ananatis YT11 and Pseudomonas fluorescens ABc9

Abstract: The influence of bacterial suspension concentration on biocontrol efficacies and storage stabilities of three biocontrol agents, including Bacillus cereus AR156, Pantoea ananatis YT11 and Pseudomonas fluorescens ABc9, were studied. The results indicated that biocontrol efficacy and storage stability did not increase along with the enhancement of the concentration of biocontrol agents, and 10 9 CFU ml -1 of the strain P. fluorescens ABc9, 10 8 CFU ml -1 of B. cereus AR156 and 10 8 CFU ml -1 of P. ananatis YT11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The matrix protects the bacteria inside [48]. It has been confirmed that the nutrient composition, buffer salts, rehydration temperature, and pH of the rehydration medium can affect the recovery of the bacteria [49]. Among them, the addition of relevant components of the growth medium to the rehydration medium is beneficial to the recovery of the viability of the bacterium [50].…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 97%
“…The matrix protects the bacteria inside [48]. It has been confirmed that the nutrient composition, buffer salts, rehydration temperature, and pH of the rehydration medium can affect the recovery of the bacteria [49]. Among them, the addition of relevant components of the growth medium to the rehydration medium is beneficial to the recovery of the viability of the bacterium [50].…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 97%